2008
DOI: 10.1007/s00467-008-0814-1
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab treatment for severe steroid- or cyclosporine-dependent nephrotic syndrome: a multicentric series of 22 cases

Abstract: Several case reports suggest that rituximab (RTX) could be effective in steroid-dependent nephrotic syndrome, but RTX efficacy has not yet been studied in a series of patients. Safety and efficacy of RTX were assessed in a multicenter series of 22 patients aged 6.3-22 years with severe steroid-dependent nephrotic syndrome or steroid-resistant but cyclosporin-sensitive idiopathic nephrotic syndrome. Patients were treated with two to four infusions of RTX. Seven patients were nephrotic at the time of RTX treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
215
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(228 citation statements)
references
References 35 publications
6
215
2
5
Order By: Relevance
“…There have been many reports recently of the steroid-sparing effect of RTX in NS [4][5][6][7][8], suggesting that not only T cells but also B cells may play a role in the pathogenesis of NS. The mechanism of RTX action in NS treatment is also unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been many reports recently of the steroid-sparing effect of RTX in NS [4][5][6][7][8], suggesting that not only T cells but also B cells may play a role in the pathogenesis of NS. The mechanism of RTX action in NS treatment is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a single infusion of RTX can delete B cells for only about 5 months [4][5][6][7][8]. Thus, the establishment of a proper treatment protocol, such as the number of RTX infusions, timing of the introduction of RTX, and how to taper the PSL dose, is desired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This summary is based on five case reports and 22 patients enrolled in a prospective multicenter trial [9,[14][15][16][17][18]. Patients enrolled in this multicenter trial suffered from frequently relapsing nephrotic syndrome necessitating intensive immunosuppressive therapy, including glucocorticoids, calcineurin inhibitors, cyclophosphamide, levamisol, and MMF, which was either not effective in inducing lasting remission and/or associated with severe drug toxicity [17].…”
Section: Methodsmentioning
confidence: 99%